Dual Mode Module as New Innovation in Learning Chemistry: Project Based Learning Oriented - Apriwanda N., Wimbi; Mahanan, Mangai Solomon; Ibrahim, Nor Hasniza; Surif, Johari; Osman, Sharifa; Bunyamin, Muhammad Abd Hadi (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Chemistry is branch of science that is different because of chemical representations. The chemical representation made students assumed that chemistry is difficult. Students must master chemical representation to be able understand chemistry deeply. Besides, science process skills are crucial skills in learning chemistry, however, the students’ science process skills are rare to be involved. Chemical representation and science process skills have relationship each other. Nowadays, it was still difficult to find module could be used either face-to-face learning or online learning. Therefore, this study aimed to develop valid module integrated chemical representation and science process skills, and can be used in face-to-face learning and online learning (dual mode module) and to investigate teachers’ response about module. The research design used was ADDIE, data collected by using online validation form that was given to 6 validators to assess module based on suitability content, potential effectiveness, and overall satisfaction. To investigate chemistry teachers’ response to module, the online questionnaire given to teachers and it was further analyzed using percentage and compare to criteria of validity and criteria of response user. Th result found that module developed is valid with suitability content is 90.7%, potential effectiveness is 92%, and overall satisfaction is 92.5%. The chemistry teachers’ response showed that this module is very good criteria (92.36%). Therefore, dual mode module hopefully would be used in learning chemistry as media in face-to-face learning and online learning and also support chemical representation and science process skills among students.